RANCANG BANGUN SISTEM INFORMASI AKADEMIK BERBASIS WEBSITE SDN CIPADU 2 MENGGUNAKAN METODE EXTREME PROGRAMMING - Gadis Gladys Sembel; Ines Heidiani Ikasari (CV. Multi Kreasi Media, 2024)
Information technology has become something that we often encounter in everyday life. In the world of Education, computerized information systems are needed to help the teaching and learning process and process related data in the educational environment such as academic data processing. This also causes parents to not be able to check their son/daughter's grades at school every time. Problems that often occur in SDN CIPADU 2 include limitations in processing and presenting data and information related to the teaching and learning process. The delay in finding student data occurred because the staff and teachers had to look for data in the administrative archives. The web-based school academic information system is an innovative problem solving tool that occurs at SDN CIPADU 2, because with the school's web-based academic information system, students and guardians can easily access student data and grades. And the data search is faster.